Dividend Decisions with Reference to SMC Global Securities Limited - Mrs. J. Madhavilatha,; Mrs. B. Shivalakshmi, (The journal of contemporary issues in business and government, 2019)
The Dividend Decision, in corporate finance, is a decision made by the directors of a company. It relates to the amount and timing of any cash payments made to the company's stockholders. The decision is an important one for the firm as it may influence its capital structure and stock price. In addition, the decision may determine the amount of taxation that stockholders pay. There are three main factors that may influence a firm's dividend decision: Free-cash flow Dividend clienteles Information signaling The free cash flow theory of dividendstheory, the dividend decision is very simple. The firm simply pays out, as dividends, any cash that is surplus after it invests in all available positive net present value projects.Dividend clientelesis a particular pattern of dividend payments may suit one type of stock holder more than another. A retiree may prefer to invest in a firm that provides a consistently high dividend yield, whereas a person with a high income from employment may prefer to avoid dividends due to their high marginal tax rate on income. If clienteles exist for particular patterns of dividend payments, a firm may be able to maximize its stock price and minimize its cost of capital by catering to a particular clientele. This model may help to explain the relatively consistent dividend policies followed by most listed companies.